Stroke in the 21st Century: A Snapshot of the Burden, Epidemiology, and Quality of Life. (27th November 2018) - Donkor, Eric S.
Abstract : Stroke is ranked as the second leading cause of death worldwide with an annual mortality rate of about 5.5 million. Not only does the burden of stroke lie in the high mortality but the high morbidity also results in up to 50% of survivors being chronically disabled. Thus stroke is a disease of immense public health importance with serious economic and social consequences. The public health burden of stroke is set to rise over future decades because of demographic transitions of populations, particularly in developing countries. This paper provides an overview of stroke in the2 1 s t century from a public health perspective.